Balancing structural formability and lattice microstrain in methylammonium-free wide bandgap perovskites - Wenting Zheng; Keonwoo Park; Joo-Hong Lee; Hae-Jun Seok; Sung-Kwang Jung; Seung-Gu Choi; Han-Ki Kim; Hyojung Ahn; Jin-Wook Lee (JPhys Energy)
State-of-the-art wide bandgap perovskite compositions for perovskite/silicon tandem solar cells often incorporate methylammonium (MA) containing multi-cation-mixed-halides compositions to achieve high efficiency. However, the MA-containing perovskite films and devices are likely to suffer from photo and thermal instability due to volatile MA ^+ cations. Here, systematic investigation on MA-free FA _1– _x Cs _x PbI _3– _y Br _y perovskite compositions was conducted to devise an effective MA-free wide bandgap composition. The Cs ^+ content was found to play a central role in optimizing the purity and stability of the desired perovskite phase. With varying Cs ^+ contents, a trade-off between structural formability of the perovskite phase and lattice microstrain was observed. Balancing the sacrificial trade-off was found to be critical in minimizing the trap densities to achieve high performance and stable wide bandgap perovskite solar cells. Our findings provide insights into the development of an optimal perovskite composition for high efficiency and stable perovskite-based tandem solar cells.